Plastic design of orthotropic annular plates - Kumar V. (My University, 2025)
This paper presents the limit analysis of orthotropic annular plates subjected to axially symmetric loading, using Modified Tresca's yield criterion and its associated flow rule. The problem has been analysed for four different boundary conditions: simply supported or clamped at both edges and simply supported at one edge and clamped at the other edge. The paper presents the design charts for uniform loading and for the four edge conditions of the plate.